Study on the Gut content and feeding apparatus of Diadema setosum - Arinah, Binti Masli (Universiti Malaysia Sarawak, UNIMAS, 2012)
Diadema setosum is a species of sea urchin that can be found extensively in Malaysia coastal water. The harvesting of sea urchins for their gonads is an economically important activity and has local value in food industry especially in Sabah. Besides that, D. setosum plays an important role in the grazing of algae. Therefore, the biology and dynamics of sea urchin populations have received considerable attention in recent years but the basic knowledge of sea urchin is still poor in Malaysia in order to manage the sea urchin resources sustainably. Hence, this study was designed (1) to document the gut content of sea urchin, (2) to determine the correlation between dry weight of gut content and (3) correlation between length of demipyramid (feeding apparatus) and test diameter. Results showed that the most abundant material in gut content of sea urchin was plant materials (52%) and the lowest was animal materials (spines; test urchins) (3